Aluminum alloy plate

The aluminum alloy plate, with a substrate containing specific Fe and Mn content and a chemical conversion film, addresses the challenges of adhesion and vibration damping in vehicle bodies, achieving high strength and effective vibration damping.

JP7653324B2Active Publication Date: 2025-03-28UACJ CORP
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2021120641
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-07-21
Publication Date
2025-03-28
Estimated Expiration
2041-07-21

AI Technical Summary

Technical Problem

Existing aluminum alloy sheets used in vehicle bodies face challenges in achieving both excellent adhesion with coating films and resins, and effective vibration damping properties, while maintaining high strength.

Method used

An aluminum alloy plate with a substrate containing specific chemical components (0.10% to 3.0% by mass of Fe and Mn) and a chemical conversion film on at least one surface, which is heat-treated to achieve Young's modulus of 70GPa or more, 0.2% resistance of 100MPa or more, and a damping rate of 1.5×10^-3 for free vibration.

Benefits of technology

The aluminum alloy plate exhibits improved adhesion to coating films and resins, high strength, and excellent vibration damping properties after heat treatment, making it suitable for vehicle body applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007653324000003
    Figure 0007653324000003
  • Figure 0007653324000004
    Figure 0007653324000004
  • Figure 0007653324000005
    Figure 0007653324000005
Patent Text Reader

Abstract

To provide an aluminum alloy sheet having excellent adhesion and vibration-damping properties with a coated film or a resin and having high strength.SOLUTION: There is provided an aluminum alloy sheet 1 which has a base material 2 having a chemical composition comprising 0.10 mass% or more and 3.0 mass% or less of Fe, 0.10 mass% or more and 3.0 mass% or less of Mn and the balance Al with inevitable impurities and a chemical conversion film 3 provided on at least one surface of the base material 2. The aluminum alloy sheet 1 has a Young's modulus after heating at a temperature of 100°C or more and 300°C or less for 0.5 hour or more and 10 hours or less of 70 GPa or more, a 0.2% proof stress of 100 MPa or more and a decrement in damped free vibration of 1.5×10-3 or more.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an aluminum alloy sheet. [Background technology]

[0002] Conventionally, steel materials have been used for automobile bodies. Car bodies are painted for the purpose of preventing rust and improving design. However, in order to respond to the recent progress in the electrification of automobiles and the increasing demand for further improvement in fuel efficiency, there is a strong demand for further weight reduction of automobile bodies. Therefore, aluminum alloy materials have started to be used for automobile bodies instead of steel materials.

[0003] As aluminum alloy materials used in automobiles, plate materials made of Al-Mg based alloys (e.g., Patent Document 1) and Al-Mg-Si based alloys (e.g., Patent Document 2), which have relatively high strength among aluminum alloys, are widely used. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] Japanese Patent Application Publication No. 8-165538 [Patent Document 2] Japanese Patent Application Publication No. 11-71623 Summary of the Invention [Problem to be solved by the invention]

[0005] When an automobile is traveling, various vibrations occur, such as vibrations generated by the power source and vibrations caused by unevenness of the road surface. If the vibrations during traveling are transmitted to various parts of the vehicle through the vehicle body, etc., problems caused by the vibrations may occur. Therefore, it is desired to further improve the vibration damping properties of Al-Mg and Al-Mg-Si alloys used in vehicles.

[0006] Furthermore, when an aluminum alloy material is used for a body panel or the like, it is desirable that the coating film has excellent adhesion to the aluminum alloy material. As a method for improving the adhesion to the coating film, for example, a method of subjecting the aluminum alloy material to a chemical conversion treatment and providing a chemical conversion coating on the surface of the aluminum alloy material is considered. However, when the chemical composition of an aluminum alloy material made of an Al-Mg alloy or an Al-Mg-Si alloy is changed to improve the vibration damping property, the type of intermetallic compound present in the alloy is changed, and it may become difficult to apply a uniform surface treatment to the surface of the aluminum alloy material.

[0007] The present invention has been made in view of the above background, and aims to provide an aluminum alloy sheet which has excellent adhesion to coatings and resins, excellent vibration damping properties, and high strength. [Means for solving the problem]

[0008] One aspect of the present invention is a substrate having a chemical composition containing Fe (iron): 0.10 mass% to 3.0 mass% and Mn (manganese): 0.10 mass% to 3.0 mass%, with the remainder being Al (aluminum) and unavoidable impurities; A chemical conversion coating is provided on at least one surface of the substrate, After heating at a temperature between 100°C and 300°C for 0.5 hours to 10 hours, the Young's modulus is 70 GPa or more, the 0.2% proof stress is 100 MPa or more, and the damping ratio in damped free vibration is 1.5×10 -3 The aluminum alloy plate has the above-mentioned properties. Effect of the Invention

[0009] The aluminum alloy sheet has a substrate having the specific chemical composition and a chemical conversion coating provided on at least one surface of the substrate. By setting the chemical composition of the substrate within the specific range, the aluminum alloy sheet can form a uniform chemical conversion coating on the substrate. By providing the chemical conversion coating on the substrate, the aluminum alloy sheet can improve adhesion to a coating film or a resin.

[0010] Furthermore, the aluminum alloy sheet has at least the specific chemical components, and thus the Young's modulus, 0.2% proof stress, and damping rate of damped free vibration can be within the specific ranges after heating for 0.5 to 10 hours at a temperature of 100° C. to 300° C. An aluminum alloy sheet having such characteristics can exhibit high strength and excellent vibration damping properties after heat treatment for baking a coating film, for example.

[0011] As described above, according to the above-mentioned embodiment, it is possible to provide an aluminum alloy sheet having excellent adhesion to coating films and resins, excellent vibration damping properties, and high strength. [Brief description of the drawings]

[0012] [Figure 1] FIG. 1 is a cross-sectional view showing a main part of an aluminum alloy plate in an embodiment. [Diagram 2] FIG. 2 is an explanatory diagram that shows a schematic diagram of a measuring device for the attenuation rate in the examples. [Diagram 3] FIG. 3 is an explanatory diagram showing a method of calculating the attenuation rate in the embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] (Aluminum alloy plate) The aluminum alloy sheet has a substrate and a chemical conversion coating provided on one or both sides of the substrate.

[0014] [Base material] First, the chemical components of the substrate of the aluminum alloy plate and the reasons for limiting them will be described.

[0015] Fe (iron): 0.10% by mass or more and 3.0% by mass or less The base material contains 0.10 mass% or more and 3.0 mass% or less of Fe as an essential component. Fe is mainly present in the Al matrix as second phase particles such as Al-Fe intermetallic compounds. The Al-Fe intermetallic compounds in the Al matrix improve the vibration damping properties of the aluminum alloy sheet and have the effect of improving the strength of the aluminum alloy sheet by dispersion strengthening. The remainder of Fe is present as a solid solution element in the Al matrix and has the effect of improving the strength of the aluminum alloy sheet.

[0016] The mechanism by which the vibration-damping properties of the aluminum alloy sheet are improved by the second-phase particles such as Al-Fe intermetallic compounds is, for example, as follows. That is, when vibration is applied to the aluminum alloy sheet from the outside, a viscous flow occurs at the interface between the Al matrix and the second-phase particles. It is considered that the vibration energy is absorbed by this viscous flow, and as a result, the vibration is attenuated early.

[0017] By making the Fe content in the substrate 0.10% by mass or more, the strength and vibration-damping property of the aluminum alloy sheet can be improved. From the viewpoint of further improving the vibration-damping property and increasing the strength of the aluminum alloy sheet, the Fe content in the substrate is preferably 0.40% by mass or more, and more preferably 1.0% by mass or more. If the Fe content in the substrate is less than 0.10% by mass, the number of second-phase particles such as Al-Fe intermetallic compounds formed in the substrate is insufficient, which may lead to a decrease in the strength and vibration-damping property of the aluminum alloy sheet.

[0018] In addition, by setting the Fe content in the substrate to 3.0 mass% or less, preferably 2.0 mass% or less, more preferably 1.7 mass% or less, a uniform chemical conversion coating can be easily formed on the substrate. As a result, the adhesion between the aluminum alloy sheet and the coating or resin can be improved. If the Fe content in the substrate is excessively high, coarse Al-Fe intermetallic compounds are likely to be formed in the substrate. If coarse Al-Fe intermetallic compounds are present in the substrate, the reaction around the coarse Al-Fe intermetallic compounds is likely to be promoted when forming a chemical conversion coating, and it may be difficult to form a uniform chemical conversion coating on the substrate.

[0019] Mn (manganese): 0.10% by mass or more and 3.0% by mass or less The substrate contains 0.10% by mass or more and 3.0% by mass or less of Mn as an essential component. Mn is mainly present in the Al matrix as second phase particles such as Al-Mn intermetallic compounds. The Al-Mn intermetallic compounds in the Al matrix have the effect of improving the strength and vibration damping of the aluminum alloy sheet, similar to the Al-Fe intermetallic compounds. In addition, Mn can form an Al-Fe-Mn intermetallic compound together with Fe in the substrate. The Al-Fe-Mn intermetallic compound has a small potential difference with the Al matrix, and therefore has the effect of suppressing the local cell reaction when forming a chemical conversion film. By suppressing the local cell reaction when forming a chemical conversion film, a uniform chemical conversion film can be easily formed on the substrate.

[0020] By making the Mn content in the substrate 0.10% by mass or more, preferably 0.20% by mass or more, more preferably 0.40% by mass or more, the strength and vibration-damping property of the aluminum alloy sheet can be improved and a uniform chemical conversion coating can be easily formed on the substrate. If the Mn content in the substrate is less than 0.10% by mass, the number of second-phase particles such as Al-Mn intermetallic compounds formed in the substrate becomes insufficient, which may lead to a decrease in the strength and vibration-damping property of the aluminum alloy sheet.

[0021] In addition, by setting the Mn content in the substrate to 3.0 mass% or less, preferably 2.0 mass% or less, more preferably 1.0 mass% or less, the chemical conversion coating can be formed uniformly on the substrate. As a result, the adhesion between the aluminum alloy sheet and the coating or resin can be improved. If the Mn content in the substrate is excessively high, coarse Al-Mn intermetallic compounds are likely to be formed in the substrate. The coarse Al-Mn intermetallic compounds have the effect of promoting the reaction when forming the chemical conversion coating, similar to the Al-Fe intermetallic compounds. Therefore, in this case, it may be difficult to form the chemical conversion coating uniformly on the substrate.

[0022] In addition to the essential components Fe and Mn, the substrate may further contain, as an optional component, one or more elements selected from the group consisting of Si (silicon), Cu (copper), Cr (chromium), Zn (zinc), Ti (titanium), B (boron), V (vanadium) and Ni (nickel).

[0023] ·Si: 0.10 mass% or more and 0.40 mass% or less The substrate may contain 0.10% by mass or more and 0.40% by mass or less of Si as an optional component. Si forms second phase particles such as Si particles in the substrate, and has the effect of improving the strength and vibration damping of the aluminum alloy sheet, similar to Al-Fe-based intermetallic compounds. In addition, Si can form an Al-Si-Mn-based intermetallic compound in the substrate together with Mn. The Al-Si-Mn-based intermetallic compound has a small potential difference with the Al parent phase, and therefore has the effect of suppressing the local cell reaction when forming a chemical conversion film. By suppressing the local cell reaction when forming a chemical conversion film, a uniform chemical conversion film can be easily formed on the substrate.

[0024] By setting the Si content in the substrate to 0.10 mass% or more and 0.40 mass% or less, more preferably 0.15 mass% or more and 0.30 mass% or less, the strength and vibration damping property of the aluminum alloy sheet can be further improved, and the chemical conversion coating can be more uniformly formed on the substrate.

[0025] ·Cu: 0.005 mass% or more and 0.100 mass% or less The substrate may contain 0.005% by mass or more and 0.100% by mass or less of Cu as an optional component. Cu forms second phase particles such as Al-Cu intermetallic compounds in the substrate, and has the effect of improving the strength and vibration damping of the aluminum alloy sheet, similar to Al-Fe intermetallic compounds. However, while the Al-Cu intermetallic compounds improve the vibration damping, they may precipitate at the grain boundaries of the Al matrix by heat treatment, causing intergranular corrosion. By setting the Cu content in the substrate to 0.005% by mass or more and 0.100% by mass or less, more preferably 0.010% by mass or more and 0.070% by mass or less, the strength and vibration damping of the aluminum alloy sheet can be further improved while suppressing the occurrence of intergranular corrosion.

[0026] ·Cr: 0.01 mass% or more and 1.00 mass% or less The substrate may contain 0.01% by mass or more and 1.00% by mass or less of Cr as an optional component. Cr forms second phase particles such as Al-Cr-based intermetallic compounds in the substrate, and has the effect of improving the strength and vibration damping properties of the aluminum alloy sheet, similar to Al-Fe-based intermetallic compounds.

[0027] On the other hand, if the Cr content in the substrate is excessively high, coarse Al-Cr intermetallic compounds are likely to be formed in the substrate. Since the coarse Al-Cr intermetallic compounds have the effect of promoting the reaction when forming a chemical conversion coating, if the coarse Al-Cr intermetallic compounds are present in the substrate in an excessively large amount, it may be difficult to uniformly form a chemical conversion coating on the substrate. By setting the Cr content in the substrate to 0.01% by mass or more and 1.00% by mass or less, more preferably 0.10% by mass or more and 0.50% by mass or less, the strength and vibration damping properties of the aluminum alloy sheet can be further improved, and the formation of coarse Al-Cr intermetallic compounds in the substrate can be suppressed, so that a chemical conversion coating can be more uniformly formed on the substrate.

[0028] ·Zn: 0.01 mass% or more and 0.50 mass% or less The substrate may contain 0.01% by mass or more and 0.50% by mass or less of Zn as an optional component. A part of Zn forms second phase particles in the Al matrix together with other alloying elements, and has the effect of further improving the strength and vibration damping of the aluminum alloy sheet. The remaining part of Zn dissolves in the Al matrix to lower the potential of the substrate, thereby improving the reactivity when forming a chemical conversion coating. However, if the content of Zn is excessively high, the substrate may be easily corroded. By setting the content of Zn in the substrate to 0.01% by mass or more and 0.50% by mass or less, more preferably 0.10% by mass or more and 0.40% by mass or less, the strength and vibration damping of the aluminum alloy sheet can be further improved, and the potential of the substrate can be appropriately lowered, thereby further promoting the formation of the chemical conversion coating.

[0029] ·Ti, B and V: Total 0.005 mass% or more and 0.500 mass% or less The substrate may contain one or more elements selected from the group consisting of Ti, B, and V as an optional component. These elements have the effect of refining the grains of the ingot during the manufacturing process of the aluminum alloy plate. By setting the total content of Ti, B, and V within the specific range, the grains of the ingot can be refined and the variation in size of the second phase particles formed in the substrate can be reduced. As a result, the variation in vibration damping properties of the aluminum alloy plate can be reduced. In addition, the reduction in the variation in size of the second phase particles reduces the variation in reactivity when forming a chemical conversion coating, and the chemical conversion coating can be formed more uniformly on the substrate. From the viewpoint of further enhancing these effects, the total content of Ti, B, and V is more preferably 0.20 mass% or less.

[0030] ·Ni: 0.10% by mass or less The substrate may contain 0.10 mass% or less of Ni as an optional component. Ni forms second phase particles such as Al-Ni intermetallic compounds in the substrate, and has the effect of improving the strength and vibration damping of the aluminum alloy sheet, similar to Al-Fe intermetallic compounds. However, while Al-Ni intermetallic compounds improve vibration damping, they may become cathode sites when exposed to corrosive substances, and may promote corrosion. In addition, since Al-Ni intermetallic compounds have the effect of promoting reactions when forming a chemical conversion coating, if the number of Al-Ni intermetallic compounds present on the surface of the substrate increases, it may become difficult to uniformly form a chemical conversion coating on the substrate.

[0031] By setting the Ni content in the substrate to 0.10 mass% or less, more preferably 0.05 mass% or less, it is possible to further improve the strength and vibration damping property of the aluminum alloy sheet while suppressing the occurrence of corrosion. In addition, in this case, it is possible to more easily form a uniform chemical conversion coating on the substrate.

[0032] Other elements In addition to the above elements, the base material contains unavoidable impurities that are inevitably mixed in during the manufacturing process. Elements contained as unavoidable impurities include, for example, Zr (zirconium), Pb (lead), Ga (gallium), and Sn (tin). The content of each element as an unavoidable impurity is 0.1% by mass or less for each element, and the total content of the unavoidable impurities is 0.2% by mass or less.

[0033] [Chemical coating] A chemical conversion coating is provided on the substrate. By setting the chemical composition of the substrate within the specific range, the aluminum alloy plate can form second phase particles such as Al-Fe intermetallic compounds in the substrate. These second phase particles can improve the strength and vibration damping of the aluminum alloy plate after heating. In addition, the second phase particles formed in the substrate in the aluminum alloy plate are unlikely to hinder the dissolution reaction and cathodic reaction of aluminum in the chemical conversion treatment. Therefore, by setting the chemical composition of the substrate within the specific range, the chemical conversion coating can be uniformly formed on the substrate, and the second phase particles can improve the strength and vibration damping of the aluminum alloy plate after heating.

[0034] By providing a chemical conversion coating on a substrate, oxidation of the substrate can be suppressed. In addition, since the chemical conversion coating has fine irregularities on the surface, it is possible to improve adhesion to coating films and resins by the anchor effect. From the viewpoint of further enhancing the effect of improving adhesion to coating films and resins, the coating weight of the chemical conversion coating is set to 2 mg / m 2 It is preferable that the concentration is 4 mg / m or more. 2 More preferably, it is 5 mg / m or more. 2 It is more preferable that the coating weight of the chemical conversion coating is 3000 mg / m or more. On the other hand, if the coating weight of the chemical conversion coating is excessively high, the chemical conversion coating is more likely to undergo cohesive failure, which may lead to a decrease in adhesion to the paint film or resin. Furthermore, in this case, the time required for the chemical conversion treatment becomes longer, which may lead to a decrease in productivity. From the viewpoint of more reliably avoiding these problems, the coating weight of the chemical conversion coating is preferably 3000 mg / m or more. 2 It is preferable that:

[0035] Examples of the chemical conversion coating include various coatings such as a zinc phosphate coating formed by a zinc phosphate treatment, a zirconium phosphate coating formed by a zirconium phosphate treatment, a zirconium oxide coating formed by a zirconium oxide treatment, a titanium phosphate coating formed by a titanium phosphate treatment, and a Ti-Zr based coating containing at least one of an oxide of Ti and a hydroxide of Ti, and at least one of an oxide of Zr and a hydroxide of Zr.

[0036] From the viewpoint of further improving the adhesion between the aluminum alloy sheet and the coating film or resin, it is preferable that the chemical conversion coating contains one or more elements selected from the group consisting of Zn (zinc), P (phosphorus), Zr (zirconium) and Ti (titanium). From the same viewpoint, when the chemical conversion coating contains Zr, the content of Zr is 2 mg / m 2 It is preferable that the concentration is 5 mg / m or more. 2 It is more preferable that the Zr content in the chemical conversion coating is 50 mg / m or more. On the other hand, if the Zr content in the chemical conversion coating is too high, the chemical conversion coating is more likely to undergo cohesive failure, which may lead to a decrease in adhesion to the paint film or resin. Furthermore, in this case, the time required for the chemical conversion treatment is longer, which may lead to a decrease in productivity. From the viewpoint of more reliably avoiding these problems, the Zr content in the chemical conversion coating is preferably 50 mg / m or more. 2 It is preferable that:

[0037] In addition, when the chemical conversion coating contains Zn, the Zn content is set to 200 mg / m from the viewpoint of further improving the adhesion between the aluminum alloy sheet and the coating film or resin. 2 More preferably, it is 250 mg / m or more. 2 It is more preferable that the Zn content in the chemical conversion coating is 3000 mg / m or more. On the other hand, if the Zn content in the chemical conversion coating is excessively high, the chemical conversion coating is more likely to undergo cohesive failure, which may lead to a decrease in adhesion to the paint film or resin. Furthermore, in this case, the time required for the chemical conversion treatment is longer, which may lead to a decrease in productivity. From the viewpoint of more reliably avoiding these problems, the Zn content in the chemical conversion coating is preferably 3000 mg / m or more. 2 It is preferable that:

[0038] [Physical properties of aluminum alloy sheets] The aluminum alloy plate has a Young's modulus of 70 GPa or more, a 0.2% proof stress of 100 MPa or more, and a damping ratio in damped free vibration of 1.5×10 after heating at a temperature of 100° C. or more and 300° C. or less for 0.5 hours or more and 10 hours or less. -3It has the above characteristics. Aluminum alloy sheets with high Young's modulus and damping rate in damped free vibration can efficiently damp externally applied vibration. Furthermore, aluminum alloy sheets with high 0.2% proof stress can improve the rigidity of final products such as automobile bodies, and can also suppress the occurrence of cracks and wrinkles during molding.

[0039] Therefore, an aluminum alloy sheet having Young's modulus, 0.2% proof stress and damping rate of damped free vibration each within the above-mentioned specific range after heating under the above-mentioned specific conditions can exhibit high strength and excellent vibration damping properties after heat treatment such as baking after painting. An aluminum alloy sheet having such properties is particularly suitable for automobile bodies.

[0040] From the viewpoint of further improving the vibration damping property of the aluminum alloy plate, the aluminum alloy plate is preferably heated at a temperature of 100° C. or more and 300° C. or less for 0.5 hours or more and 10 hours or less, and the damping rate of the damped free vibration of the aluminum alloy plate is 2.0×10 -3 It is more preferable that the damping rate is equal to or higher than this. Note that a specific method for measuring the damping rate of damped free vibration will be described in detail in the Examples.

[0041] [Application] As described above, the aluminum alloy plate can improve adhesion to paint films and resins by setting the chemical composition of the substrate within the specific range and providing a chemical conversion coating on the substrate. Moreover, the aluminum alloy plate has high strength and excellent vibration damping properties after heating. Therefore, the aluminum alloy plate is suitable for applications requiring high strength and excellent vibration damping properties after paint baking, such as automobile body panel materials.

[0042] When the aluminum alloy sheet is heated during paint baking or the like, it is preferable that the heating temperature is 300° C. or less and the heating time is 10 hours or less. If the heating temperature of the aluminum alloy sheet is excessively high and if the heating time is excessively long, the strength of the aluminum alloy sheet may be reduced.

[0043] (Method of manufacturing aluminum alloy plate) In producing the aluminum alloy plate, a substrate made of an aluminum alloy having the specific chemical composition is cold-rolled to a desired thickness, and then the substrate is subjected to a chemical conversion treatment to form a chemical conversion coating.

[0044] The method for producing the substrate is not particularly limited. For example, the substrate may be produced by producing an ingot having the specific chemical composition by DC casting, and then, if necessary, heating the ingot to perform homogenization treatment, and then hot rolling.

[0045] The cooling rate of the ingot after casting in DC casting is preferably in the range of 0.1° C. / sec to 1000° C. / sec. When homogenization treatment is performed, the ingot is held at a temperature of 500° C. to 650° C. for 0.5 hours or more.

[0046] When hot rolling is performed on an ingot without homogenization treatment, it is preferable to start rolling while the temperature of the ingot is in the range of 300° C. to 550° C. When hot rolling is performed on an ingot after homogenization treatment, it is preferable to start rolling while the temperature of the ingot is in the range of 300° C. to less than 380° C. In either case, the temperature of the base material at the completion of hot rolling may be 100° C. to less than 380° C.

[0047] In addition, a plate material having the specific chemical composition produced by CC casting can be used as the substrate. The cooling rate of the substrate after casting in CC casting is preferably in the range of 0.1° C. / sec to 1000° C. / sec.

[0048] The thus obtained substrate is subjected to cold rolling to reduce the thickness of the substrate to a desired thickness. The thickness of the substrate after cold rolling may be appropriately set within a range of, for example, 1.0 mm or more and 2.0 mm or less. In addition, the total rolling ratio in the cold rolling, that is, the ratio of the thickness reduction of the substrate by cold rolling to the thickness of the substrate before cold rolling, is preferably 10% or more and 95% or less.

[0049] In addition, when the base material is cold-rolled, the base material may be heated and annealed as necessary. Annealing may be performed before cold rolling or during cold rolling. Annealing may be performed both before cold rolling and during cold rolling. When performing annealing, a batch annealing furnace or a continuous annealing furnace may be used. For example, when performing annealing using a batch annealing furnace, it is preferable to hold the base material at a temperature of 200°C or more and less than 380°C for 0.1 hours or more and 10 hours or less.

[0050] By subjecting the substrate after the cold rolling to a chemical conversion treatment, a chemical conversion coating is formed on the substrate, and the aluminum alloy sheet can be obtained. In the chemical conversion treatment, when the substrate is brought into contact with a chemical conversion treatment liquid, a dissolution reaction of aluminum on the substrate surface and a corresponding cathodic reaction proceed in parallel. Then, the pH of the chemical conversion treatment liquid increases with these reactions, and a chemical conversion coating is formed on the substrate.

[0051] The chemical conversion treatment may be performed at any time between the completion of cold rolling and the coating. For example, the chemical conversion treatment may be performed by bringing a substrate wound into a coil into contact with a chemical conversion treatment liquid while pulling it out of the coil. The chemical conversion treatment may also be performed by bringing a substrate cut to a desired size or a substrate after forming into contact with a chemical conversion treatment liquid. The chemical conversion treatment liquid used for the chemical conversion treatment may be determined according to the desired chemical conversion film, the reactivity between the substrate and the chemical conversion treatment liquid, the surface shape of the substrate, and the like. The treatment time in the chemical conversion treatment may be appropriately set according to the desired amount of the chemical conversion film attached. EXAMPLES

[0052] An embodiment of the aluminum alloy plate will be described with reference to Figs. 1 to 3. As shown in Fig. 1, the aluminum alloy plate 1 of this embodiment has a base material 2 having a chemical composition containing Fe: 0.10 mass% to 3.0 mass% and Mn: 0.10 mass% to 3.0 mass% with the balance being Al and unavoidable impurities, and a chemical conversion coating 3 provided on at least one surface of the base material 2. Furthermore, as shown in Table 1, the aluminum alloy plate 1 of this embodiment has a Young's modulus of 70 GPa or more, a 0.2% proof stress of 100 MPa or more, and a damping rate in damped free vibration of 1.5 x 10 after heating at a temperature of 100°C to 300°C for 0.5 hours to 10 hours. -3 The above characteristics are achieved.

[0053] In producing the aluminum alloy plate 1 of this example, first, an ingot having the chemical composition shown in Table 1 is produced by DC casting. In Table 1, the symbol "Bal." indicates that the relevant element is the remainder, and the symbol "-" indicates that the relevant element is not included. After the surface of the ingot is chamfered to remove the surface segregation layer, the ingot is held at a temperature of 520°C for 1 hour for homogenization treatment. Thereafter, hot rolling is started with the ingot temperature at 460°C to produce a base material 2 having a thickness of 3.0 mm. The temperature of the base material 2 at the completion of the hot rolling is 280°C. Next, the base material 2 is cold rolled to reduce the thickness of the base material 2 to 1.0 mm.

[0054] The substrate 2 thus obtained is immersed in a 5% by mass aqueous sulfuric acid solution at a temperature of 45° C. to remove the natural oxide film formed on the surface of the substrate 2. The substrate 2 is taken out of the aqueous sulfuric acid solution, washed with water, and then immersed in an aqueous solution containing hexafluorozirconic acid to perform a chemical conversion treatment. In this way, a zirconium-based chemical conversion film 3 containing Zr is formed on the substrate 2, and the test material S1 shown in Table 1 can be obtained.

[0055] Test materials R1 to R3 shown in Table 1 are test materials for comparison with test material S1. Test material R1 has the same configuration as test material S1, except that the chemical composition of the substrate is changed as shown in Table 1. Test materials R2 and R3 have the same configuration as test material S1, except that the chemical composition of the substrate is changed as shown in Table 1 and the chemical conversion coating is a zinc-based chemical conversion coating containing Zn.

[0056] The Young's modulus, 0.2% proof stress and damping rate of damped free vibration of the aluminum alloy plate 1 of this example after heating were measured as follows.

[0057] ·Young's modulus and damping rate After each test material is heated at the holding temperature and holding time shown in Table 2 and heat-treated, a strip-shaped test piece 80 mm long and 8 mm wide is taken from the test material so that the rolling direction and the longitudinal direction are parallel. The test piece is attached to a free resonance type internal friction measuring device ("JE-RT" manufactured by Nippon Technoplus Co., Ltd.), and the Young's modulus and damping rate are measured by the damping method. The measuring device 4 used in this example has a driving electrode 41 and an amplitude sensor 42 facing the driving electrode 41, as shown in FIG. 2. The test piece S is horizontally placed between the driving electrode 41 and the amplitude sensor 42, and the test piece S is fixed by a thin wire 43 at a position that is a node of the vibration. In this state, an alternating current is applied to the driving electrode 41 to apply a Coulomb force to the test piece S, thereby vibrating the test piece S. Then, the amplitude sensor 42 is used to measure the amplitude of the test piece S, and a vibration waveform can be obtained.

[0058] In this example, an AC current is applied to the driving electrode 41 to forcibly vibrate the test piece S, and then the AC current is stopped and the test piece S is allowed to vibrate freely due to the restoring force. The vibration of the test piece S is a so-called damped free vibration in which the amplitude exponentially decays while oscillating periodically with a period T, as shown in the waveform in Fig. 3. Note that in the damped free vibration, it is believed that the amplitude exponentially decreases due to loss of vibration energy caused by resistance due to the atmosphere and internal friction due to dislocations and grain boundaries inside the test piece.

[0059] The method for calculating the value of the damping rate δ is as follows. First, the nth period (where n is a positive integer) and the n+mth period (where m is an integer of 2 or more) are arbitrarily selected from the waveform of the damped free vibration, and the amplitude a n and the amplitude a of the n+mth period n+m The decay rate δ is the amplitude a k and the amplitude of the next period a k+1 The natural logarithm of the ratio ln(a k / a k+1 ), so the amplitude a n and the amplitude a n+m The natural logarithm of the ratio ln(a n / a n+m ) can be expanded as follows: ln(a n / a n+m )=ln{(a n / a n+1 )×(a n+1 / a n+2 )×···×(a n+m-1 / a n+m )}=mδ

[0060] Therefore, the value of the damping rate δ is the amplitude a n and the amplitude a of the n+mth period n+m Using the values ​​of δ=(1 / m)·ln(a n / a n+m )

[0061] The Young's modulus after heating and the damping rate of damped free vibration for each test material are shown in Table 2. Note that the damping rate was not calculated for test material S2, test material S3, test material R2, and test material R3, so the symbol "-" is entered in the damping rate column.

[0062] ·0.2% yield strength Each test material is heated and heat-treated at the holding temperature and holding time shown in Table 2, and then a JIS No. 5 test piece is taken from the test material so that the rolling direction and the longitudinal direction are parallel. A tensile test is performed using this test piece according to a method conforming to JIS Z2241:2011. Then, the 0.2% proof strength of each test material is calculated based on the load-displacement curve obtained from the tensile test. Table 2 shows the 0.2% proof strength of each test material after heating.

[0063] [Table 1]

[0064] [Table 2]

[0065] As shown in Table 1, the test material S1 has a substrate 2 having the specific chemical components and a chemical conversion coating 3 provided on the substrate 2, and therefore has excellent adhesion to paint films and resins. Furthermore, the test material S1 has properties such that the Young's modulus, 0.2% proof stress, and damping rate of damped free vibration are each within the specific ranges after heat treatment at the temperature and time shown in Table 2. An aluminum alloy sheet having such properties is suitable for use in automobile bodies, for example, because it can exhibit high strength and excellent vibration damping properties after heating such as paint baking.

[0066] In the test material R1, the Fe content and the Mn content in the substrate are less than the specific ranges, so that second phase particles such as Al-Fe intermetallic compounds and Al-Mn intermetallic compounds are less likely to form in the substrate, and therefore the Young's modulus and damping rate after heating are low, and the vibration damping property is inferior to that of the test material S1.

[0067] Test materials R2 and R3 have Fe and Mn contents in the base material that are lower than the specific ranges, and the heat treatment temperature is too high, so that they have lower strength than test material S1.

[0068] The above describes examples of specific configurations of the aluminum alloy plate according to the present invention, but the specific configurations of the aluminum alloy plate according to the present invention are not limited to the configurations of the examples, and the configurations can be changed as appropriate within the scope that does not depart from the spirit of the present invention. [Explanation of symbols]

[0069] 1. Aluminum alloy plate 2 Base material 3. Chemical Coating

Claims

1. A base material having a chemical composition containing Fe: 0.10 mass% or more and 3.0 mass% or less, Mn: 0.10 mass% or more and 3.0 mass% or less, with the balance being Al and unavoidable impurities; A chemical conversion coating is provided on at least one surface of the substrate, After heating at a temperature of 100° C. or more and 300° C. or less for 0.5 hours or more and 10 hours or less, the Young's modulus is 70 GPa or more, the 0.2% proof stress is 100 MPa or more, and the damping rate in damped free vibration is 1.5×10 -3 The aluminum alloy plate has the above characteristics.

2. The base material further contains one or more elements selected from the group consisting of Si: 0.10 mass% or more and 0.40 mass% or less, Cu: 0.005 mass% or more and 0.100 mass% or less, Cr: 0.01 mass% or more and 1.00 mass% or less, and Zn: 0.01 mass% or more and 0.50 mass% or less. The aluminum alloy plate according to claim 1.

3. The base material further contains one or more elements selected from the group consisting of Ti, B and V, and the total content of these elements is 0.005 mass% or more and 0.500 mass% or less. The aluminum alloy plate according to claim 1 or 2.

4. The aluminum alloy plate according to any one of claims 1 to 3, wherein the substrate further contains Ni: 0.10 mass% or less.

5. The coating weight of the chemical conversion coating is 2 mg / m 2 The aluminum alloy plate according to any one of claims 1 to 4.

6. The aluminum alloy sheet according to any one of claims 1 to 5, wherein the chemical conversion coating contains one or more elements selected from the group consisting of Zn, P, Zr and Ti.

7. The chemical conversion coating has a thickness of 2 mg / m 2 The aluminum alloy sheet according to any one of claims 1 to 6, containing the above Zr.

8. The chemical conversion coating has a thickness of 200 mg / m 2 The aluminum alloy sheet according to any one of claims 1 to 7, containing the above Zn.

Citation Information

Patent Citations

  • Vibration attenuation type aluminum alloy and preparation method thereof

    CN105648287A

  • High strength aluminum alloy plate for printing plate

    JP1985063342A

  • Rolled aluminum alloy sheet for automobile body sheet, improved in recycling property, and production thereof

    JP1996165538A

  • Aluminum alloy sheet for automotive body panel and its production

    JP1999071623A

  • Aluminum material and manufacturing method therefor

    JP2018123382A